Does Croatia Need a General Anti-Avoidance Rule? Recommended Changes to Croatia’s Current Legislative Framework - Rebecca Prebble (Financial Theory and Practice, 2005)
This paper considers whether Croatia would benefit from the introduction of a general anti-avoidance rule into its tax system. The paper gives an overview of what tax avoidance is and differentiates the concept from the related concepts of tax evasion and fraud. The paper then describes how general anti-avoidance rules work. The paper gives an overview of Croatia’s tax system, including the measures the country already has to combat tax avoidance, and concludes that a general anti-avoidance rule is necessary. The paper draws on the experiences of countries with legal systems similar to that of Croatia to suggest the form that a Croatian general anti-avoidance rule should take.